No Contractual Obligation to Improve Education: School Boards and Their Superintendents. Issue 6 (28th August 2017) - Maranto, Robert; Trivitt, Julie; Nichols, Malachi; Watson, Angela
Abstract : Since the passage of No Child Left Behind, public schools have felt pressure to emphasize equitable academic outcomes. We investigate whether contracts agreed to by school boards and the superintendents they employ include academic and equity criteria to judge the performance of superintendents. Data come from the universe of 2013‐14 school superintendent contracts in North Carolina. Only nine of the 115 contracts include academic goals of any kind, and none include equity‐related criteria. Similarly, the universe of model superintendent contracts provided by state school boards associations (N = 20) rarely mention such criteria. Findings suggest that one reason for the relatively static equity and achievement outcomes in American public schools since the national introduction of accountability‐oriented reforms is that local school boards refuse to use academic and equity criteria to evaluate superintendents. The political science literature on elections and accountability suggests possible explanations. Related Articles: Patrick, Barbara .2016 . "Performance Policies and Workforce Development: Can the Market Model Be Successfully Implemented in the Public Arena? "Politics & Policy 44 (6 ):1116 ‐1157 .http://onlinelibrary.wiley.com/doi/10.1111/polp.12185/full Webber, David J .2010 . "School District Democracy: School Board Voting and School Performance ."Politics & Policy 38 (1 ):81 ‐95 .http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2009.00229.x/full Patrick, Barbara .2012 . "Fiscal Federalism, Performance Policies, and Education Reforms: Are States Using Performance Policies to Improve Workforce Quality? "Politics & Policy 40 (4 ):593 ‐628 .http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2012.00370.x/full